Single-cell analysis of patient-derived PDAC organoids reveals cell state heterogeneity and a conserved developmental hierarchy - Krieger, Teresa G.; Le Blanc, Solange; Jabs, Julia; Ten, Foo Wei; Ishaque, Naveed; Jechow, Katharina; Debnath, Olivia; Leonhardt, Carl-Stephan; Giri, Anamika; Eils, Roland; Strobel, Oliver; Conrad, Christian (Nature Communications, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is projected to be the second leading cause of cancer mortality by 2030. Bulk transcriptomic analyses have distinguished ‘classical’ from ‘basal-like’ tumors with more aggressive clinical behavior. We derive PDAC organoids from 18 primary tumors and two matched liver metastases, and show that ‘classical’ and ‘basal-like’ cells coexist in individual organoids. By single-cell transcriptome analysis of PDAC organoids and primary PDAC, we identify distinct tumor cell states shared across patients, including a cycling progenitor cell state and a differentiated secretory state. Cell states are connected by a differentiation hierarchy, with ‘classical’ cells concentrated at the endpoint. In an imaging-based drug screen, expression of ‘classical’ subtype genes correlates with better drug response. Our results thus uncover a functional hierarchy of PDAC cell states linked to transcriptional tumor subtypes, and support the use of PDAC organoids as a clinically relevant model for in vitro studies of tumor heterogeneity.
Gesehen am 23.11.2021